2013
DOI: 10.1021/jm400070u
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Hydrogen Bonding and Aromatic Stacking to the Affinity and Efficacy of Cannabinoid Receptor CB2Antagonist, 5-(4-chloro-3-methylphenyl)-1-[(4-methylphenyl)methyl]-N-[(1S,2S,4R)-1,3,3-trimethylbicyclo[2.2.1]hept-2-yl]-1H-pyrazole-3-carboxamide (SR144528)

Abstract: Despite the therapeutic promise of the sub-nanomolar affinity cannabinoid CB2 antagonist, N-[(1S)-endo-1,3,3-trimethylbicyclo[2.2.1]heptan2-yl]-5-(4-chloro-3-methylphenyl)-1-[(4-methylphenyl)methyl]-1H-pyrazole-3-carboxamide (SR144528, 1), little is known about its binding site interactions and no primary interaction site for 1 at CB2 has been identified. We report here the results of Glide docking studies in our cannabinoid CB2 inactive state model that were then tested via compound synthesis, binding and fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 53 publications
3
17
0
Order By: Relevance
“…As regards docking of SR144528, the selected binding mode resulted in a pose (Fig. 3a) in good agreement with that previously reported for the same compound [46], where the carboxamide oxygen hbonds to both K 3.28 and S 2.60 , the pyrazole ring N2 atom h-bonds to the S 7.39 side chain, the 3-methyl-4-chloro-phenyl establishes hydrophobic contacts with T 3.33 and W 5.43 residues, and the pmethyl-benzyl moiety forms further hydrophobic contacts with TM6 residues (V 6.51 , L 6.54 , M 6.55 ). Docking of the N-cycloheptyl-1- [32] showed a slight different binding mode (Fig.…”
Section: Molecular Modelling Studiessupporting
confidence: 89%
“…As regards docking of SR144528, the selected binding mode resulted in a pose (Fig. 3a) in good agreement with that previously reported for the same compound [46], where the carboxamide oxygen hbonds to both K 3.28 and S 2.60 , the pyrazole ring N2 atom h-bonds to the S 7.39 side chain, the 3-methyl-4-chloro-phenyl establishes hydrophobic contacts with T 3.33 and W 5.43 residues, and the pmethyl-benzyl moiety forms further hydrophobic contacts with TM6 residues (V 6.51 , L 6.54 , M 6.55 ). Docking of the N-cycloheptyl-1- [32] showed a slight different binding mode (Fig.…”
Section: Molecular Modelling Studiessupporting
confidence: 89%
“…For instance, docking of a series of agonists to the binding pocket of the homology model of the serotonin 5-HT 2C G protein-coupled receptor with the PatchDock server [67] produced ligand conformations interacting with tryptophan and phenylalanine residues through parallel and perpendicular aromatic stacking [68] . Another example is a molecular modeling study conducted with Glide [69] for subnanomolar affinity antagonists of the cannabinoid receptor CB 2 [70] . Docking calculations revealed a number of parallel and perpendicular aromatic contacts between chloromethylphenyl and methylbenzyl rings of the compounds and a cluster of aromatic residues in CB 2 , suggesting that π-π interactions are critical to the efficacy of these antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…[23] This study suggested that the SR144528 amide functional group is important for interacting with CB 2 R. In addition, aromatic stacking interactions in the transmembrane helix (TMH) 5-6 aromatic cluster werer evealed to be crucial to the SR144528-CB 2 Rc omplex. [23] This study suggested that the SR144528 amide functional group is important for interacting with CB 2 R. In addition, aromatic stacking interactions in the transmembrane helix (TMH) 5-6 aromatic cluster werer evealed to be crucial to the SR144528-CB 2 Rc omplex.…”
Section: Molecular Modelingmentioning
confidence: 96%
“…[23] This study suggested that the SR144528 amide functional group is important for interacting with CB 2 R. In addition, aromatic stacking interactions in the transmembrane helix (TMH) 5-6 aromatic cluster werer evealed to be crucial to the SR144528-CB 2 Rc omplex. [23][24][25][26] This homology model wasp re-equilibrated in as tearoyl-docosahexaenoylphosphatidylcholine( SDPC) bilayer for 300 ns to allow it to adjust in al ipidic environment [23] (see the Experimental Section). [24] In the current study,G lide docking studies revealed that the novel pyridazinones reported hereb ind in as imilar orientation as the 1,8-naphthyridin-2(1H)-one-3-carboxamides.…”
Section: Molecular Modelingmentioning
confidence: 96%
See 1 more Smart Citation